A European empirical study of institutional differences in IPOs anomalies - Susana Alvarez (Journal of Risk and Financial Management, 2023)
The present research shows the influence of institutional differences on the performance of initial public offerings (IPOs), both at the level of initial underpricing and at the level of 1-, 3- and 5-year performance. Our results represent a relevant empirical contribution to the international evidence because they allow us to test the influence of institutional differences on initial and long-term performance in a large database consisting of IPOs from 18 European countries, given that the European framework has been less analysed than the U.S. institutional environment. The main novelty and contribution of this research in relation to previous investigations is that those existing to date only analyse the institutional effect on the anomaly that occurs on the first day of IPO listing, i.e., underpricing, whereas this study is more ambitious; it considers the institutional effect on both underpricing and the long-term performance of the IPOs considered, which makes it possible to cover subsequent returns of up to 5 years after the start of the stock market listing. It is therefore, to our knowledge, the most comprehensive study to date on the effect of institutional factors on the two IPO anomalies: short and long term.
Keywords: 650; IPOs; underpricing; underperformance; anomalies; institutional differences